The presence of the future : the eschatology of biblical realism - Ladd, George Eldon, 1911-1982 (Eerdmans Pub. Co, 1974)
George Eldon Ladd's comprehensive treatment of New Testament eschatology has become the definitive discussion of the theological interpretation known as "inaugurated eschatology." Reflecting profound biblical insight and a balanced treatment of conflicting views, this volume convincingly develops Ladd's thesis that the kingdom of God involves two great movements -- its present fulfillment in Jesus and its future consummation in the last days. Ladd begins this revised edition (formerly titled Jesus and the Kingdom) by taking readers step by step through the findings of his predecessors and contemporaries on the great debate as to whether the kingdom of God promised by Jesus is now, in the immediate future, or in some unknown time to come. He then traces the prophetic expectation of the kingdom in the Old Testament, pursues the development of this expectation through the intertestamental literature, and, against this background, reconstructs the teaching and mission of Jesus. Ultimately, Ladd finds the key to understanding the kingdom in the concept of "the rule of God." His interpretation of the divine reign brings together the Old Testament promise of the kingdom, its fulfillment in history, and its consummation at the end of history. - Back cover.